Unruly audience: folk interventions in popular media - Kelley, Greg, author; Utah State University Press, publisher (Colorado State University. Libraries, 2020)
Analyzes ways in which folk culture appropriates and refashions familiar media texts from film, television, stand-up comedy, popular music, and tourism. Exploring popular cultural manifestations of folklore as well as the folk manipulation of materials from contemporary media, with attention to the dynamics of production and reception.--Provided by publisher.
Introduction: reception and resistance -- Colonel Bogey's parade of parody -- "There's dirty work afoot": on the reception of Disney's Snow White -- Haunting visitors: tourism, narrative, and the spectral -- "That's what she said": folk expression meets media meme -- "Your Kind of Place": brand awareness and Intervention in children's culture -- "The joke's on us": deconstructing metahumor -- Conclusion: folklore, media, and the unruly audience.
Keywords: Folklore